Features of the Earth surface deformations in the Kamchatka peninsula and their relation to geoacoustic emission - I. A. Larionov; Y. V. Marapulets; B. M. Shevtsov (Solid Earth, 2014)
The paper presents the results of investigations of deformation processes in the near-surface sedimentary rocks, which have been carried out in a seismically active region of the Kamchatka peninsula since 2007. The peculiarity of the experiments on registration of geodeformations is the application of a laser strainmeter–interferometer constructed according to the Michelson interferometer scheme. Besides rock deformations, geoacoustic emission in the frequency range from several hertz to the first tens of kilohertz is under investigation. Piezoceramic hydrophones installed in artificial water reservoirs are applied. It is shown that periods of primary rock compression and tension with a duration of up to several months are distinguished in the geodeformation process at the observation site. During the direction change in the deformations, when the geodeformation process rate grows, an increase in geoacoustic radiation is observed.